Pengaruh Jangka Waktu Pemanasan terhadap Karakteristik Minyak Kelapa Murni (Virgin Coconut Oil) - Kelik Putranto; Amila Khairina; Tharisa Anggraeni (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2022)
Coconut (Cocos nucifera) has a strategic role for the people of Indonesia, considering that its product is one of the nine staples of society, namely coconut oil. One type of coconut oil that is beneficial for health and cosmetics is virgin coconut oil. Research on virgin coconut oil has been carried out from April to May 2022 at the Chemical and Processing Laboratory of the Faculty of Agriculture, Ma'soem University. The experimental treatments consisted of heating periods: A (3 minutes), B (4 minutes), C (5 minutes), D (6 minutes), E (7 minutes) and F (8 minutes). Each treatment tried was repeated 4 times. The method used is an experimental method using a completely randomized design (CRD) with Duncan's multiple range test statistic at a 5 percent level of significance. The results showed that the heating period of 6 minutes produced the best characteristics of virgin coconut oil. This determination is based on the content of free fatty acids, water content, color (very clear), preferred taste and aroma.